Evaluation of Suspending Properties of Cassia Roxburghii Mucilage on Sulphamethaoxazole Suspension - K.S.G. ARUL KUMARAN,; D.CHRISTOPHER VIMALSON,; S.PALANISAMY,; M. JAGADEESAN, (International Journal of Pharma and Bio Sciences, 2010)
It is evident that, plant gums and mucilage have been widely used in various industries like paper, textile, food, pharmaceuticals, ink, cosmetics, petroleum due to their abundance in nature, non-toxic, bio-degradable, ecofriendly and comparitivley cheap. They are frequently used in pharmaceuticals as thickening, binding, emulsifying, suspending, and stabilizing agents and coating materials in micro encapsulation. Various plant gums, which have been used as Suspending agents include, Acacia, Compound Tragacanth, xanthan gum. In view of importance of mucilage in pharmaceuticals for the manufacture of suspension , Cassia roxburghii seed gum (family Fabaceae/Leguminosae) were evaluated by comparing with Acacia and Compound Tragacanth gum at concentration 2.5 and 3%w/v in sulphamethoxazole suspension . The prepared suspension was evaluated for its sedimentation volume, rheology and particle size analysis. The Cassia roxburghii (filtered gum) at 2.5%w/v produced good suspendability compared to the Cassia roxburghii (Defatted gum) , Acacia and Compound Tragacanth gum. .The suspending ability of the suspending agents were in the order of cassia roxburghii (filtered gum) >Compound Tragacanth > cassia roxburghii (defatted gum) >Acacia gum. The results showed that sedimentation volume, viscosity and particle size were directly proportional to the concentration of the suspending agents. The reverse case was observed with the flow rate. The present studies indicates that Cassia roxburghii mucilage obtained by filteration method appeared to exhibit the best suspendability for sulphamethoxazole suspensions, compared with compound Tragacanth , Cassia roxburgii (defatted gum) and Acacia gum , and can be employed as stabilizer and thickener of choice in pharmaceutical suspension.